Learning from urban policy diversity and complexity: Evaluation and knowledge sharing in urban policy - Isabel Breda Vázquez (2010)
Several authors emphasise the actual diversity of urban policies and governance structures, as well as its experimental nature. On the one hand, diversity is viewed as a fundamental condition of actual urban policies. But, on the other hand, it is also viewed as a problem, which raises concerns about the coordination or integration of policies. This paper argues that evaluation procedures can be an active learning tool capable of promoting local strategic policy integration among diverse policies. An appropriate evaluation methodology, able to appraise both relational networks and normative frameworks (agendas, visions), is then proposed and tested, and its results are discussed.